Numerical Simulation Study on the Distribution Law of Deviatoric Stress of Floor under the Influence of Mining. (9th February 2021) - Liu, Hongtao; Huo, Tianhong; Li, Yongen; Luo, Ming; Zhou, Guangdong; He, Zengji
Abstract : The Zhaogu No. 2 coal mine is a single thick coal seam mining mine with high gas content. Due to the lack of protective layer mining conditions, we can only arrange the floor gas extraction roadway (FGER) to extract the gas from the overlying coal seam of the FGER to ensure safe production. However, improper placement of FGER will cause water inrush from the floor of FGER. Given above contradictions, this paper analyzes the stress-strain relationship of the fractured rock mass in the caving zone and the stress-recovery characteristics of the goaf from the perspective of the structural characteristics of the overlying strata above goaf. Based on this, a FLAC 3D numerical model of equivalent delayed filling of caving rock mass was established by using the double-yield model filling method. The distribution of floor stress under the influence of mining is obtained after the model calculation, i.e., with the increase of the distance from the floor, the ratio of bidirectional stress to the peak value, and the stability value decrease, but the decrease amplitude becomes smaller and smaller. Therefore, floor roadway used for gas extraction should be located 10-15 m below the floor. Combined with the distribution of floor strata in 11060 working face, it is finally determined that FGER should be located 13 m below the floor. Such arrangement of FGER can not only ensure the effect of gas drainage but also prevent the occurrence of water inrush from floor.